Prognostic Value of an Immunohistochemical Signature in Patients With Head and Neck Mucosal Melanoma - Xu, Qing-Qing; Li, Qing-Jie; Huang, Cheng-Long; Cai, Mu-Yan; Zhang, Mei-Fang; Yin, Shao-Han; Lu, Li-Xia; Chen, Lei (Frontiers in Immunology, 2021)
Purpose: We aimed to develop a prognostic immunohistochemistry (IHC) signature for patients with head and neck mucosal melanoma (MMHN). Methods: In total, 190 patients with nonmetastatic MMHN with complete clinical and pathological data before treatment were included in our retrospective study. Results: We extracted five IHC markers associated with overall survival (OS) and then constructed a signature in the training set (n=116) with the least absolute shrinkage and selection operator (LASSO) regression model. The validation set (n=74) was further built to confirm the prognostic significance of this classifier. We then divided patients into high- and low-risk groups according to the IHC score. In the training set, the 5-year OS rate was 22.0% (95% confidence interval [CI]: 11.2%- 43.2%) for the high-risk group and 54.1% (95% CI: 41.8%-69.9%) for the low-risk group (P<0.001), and in the validation set, the 5-year OS rate was 38.1% (95% CI: 17.9%-81.1%) for the high-risk group and 43.1% (95% CI: 30.0%-61.9%) for the low-risk group (P=0.26). Multivariable analysis revealed that IHC score, T stage, and primary tumor site were independent variables for predicting OS (all P＜0.05). We developed a nomogram incorporating clinicopathological risk factors (primary site and T stage) and the IHC score to predict 3-, 5-, and 10-year OS. Conclusions: A nomogram was generated and confirmed to be of clinical value. Our IHC classifier integrating five IHC markers could help clinicians make decisions and determine optimal treatments for patients with MMHN.